Preferences for Vaccination: Does Health Literacy Make a Difference?. (November 2015) - Veldwijk, Jorien; van der Heide, Iris; Rademakers, Jany; Schuit, A. Jantine; de Wit, G. Ardine; Uiters, Ellen; Lambooij, Mattijs S.
Purpose. The purpose of this study is to examine to what extent health literacy is associated with parental preferences concerning childhood vaccination.Methods. A cross-sectional study was conducted among 467 Dutch parents of newborns aged 6 weeks (response rate of 37%). A self-reported questionnaire was used to measure health literacy by means of Chew's Set of Brief Screening Questions, as well as parental preferences for rotavirus vaccination by means of a discrete choice experiment. Five rotavirus-related characteristics were included (i.e., vaccine effectiveness, frequency of severe side effects, location of vaccination, protection duration, and out-of-pocket costs). Panel latent class models were conducted, and health literacy and educational level were added to the class probability model to determine the association between health literacy and study outcomes.Results. Lower educated and lower health literate respondents considered protection duration to be more important and vaccine effectiveness and frequency of severe side effects to be less important compared with higher educated and higher health literate respondents. While all respondents were willing to vaccinate against rotavirus when the vaccine was offered as part of the National Immunization Program, only lower educated and lower health literate parents were willing to vaccinate when the vaccine was offered on the free market.Conclusion: Health literacy is associated with parents' preferences for rotavirus vaccination. Whether differences in vaccination decisions are actually due to varying preferences or might be better explained by varying levels of understanding should be further investigated. To contribute to more accurate interpretation of study results, it may be advisable that researchers measure and report health literacy when they study vaccination decision behavior.